2015
DOI: 10.1038/528188a
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry: Develop ionic liquid drugs

Abstract: A new realm of potential drugs is hiding in plain sight. Pharmaceutical research, manufacture and regulation focuses on solid active ingredients, delivered as powders or tablets. Liquid forms are neglected and viewed as an intermediate step, rather than an endpoint.Yet many promising solid drug candidates are too insoluble for the body to absorb. Of Develop ionic liquid drugsUpdate regulation to spur research into drugs that the body absorbs more easily and that could reach market more quickly, urge Julia L. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
141
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 8 publications
0
141
0
2
Order By: Relevance
“…In order to solve the problem, some scientists have suggested that it is of great value to replace the widely used toxic organic solvents by safely, biodegradable, and environmentally friendly neoteric solvents for the development of sustainable pharmaceutical processes . Ionic liquids (ILs) as neoteric solvents, with the advanced characteristics of non‐volatility, non‐flammability, and high recyclability, have been proposed as green solvents for the extraction, separation, crystallization, and purification of drugs . Particularly, existing experimental data showed that most of imidazolium‐based ILs were considered to be a biodegradable IL and to exhibit quite a low toxicity on human body, which made them even as the component of the active pharmaceutical ingredients (APIs) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the problem, some scientists have suggested that it is of great value to replace the widely used toxic organic solvents by safely, biodegradable, and environmentally friendly neoteric solvents for the development of sustainable pharmaceutical processes . Ionic liquids (ILs) as neoteric solvents, with the advanced characteristics of non‐volatility, non‐flammability, and high recyclability, have been proposed as green solvents for the extraction, separation, crystallization, and purification of drugs . Particularly, existing experimental data showed that most of imidazolium‐based ILs were considered to be a biodegradable IL and to exhibit quite a low toxicity on human body, which made them even as the component of the active pharmaceutical ingredients (APIs) .…”
Section: Introductionmentioning
confidence: 99%
“…For the aforementioned reasons, special attention has been given to ILs over the last few years . Studies of the effects of ILs as antitumor agents have brought new perspectives to the use of this compound class.…”
Section: Ionic Liquids As Potential Antitumor Agentsmentioning
confidence: 99%
“…[22,24] Since 2007, Room Temperature Ionic Liquids (RTILs) containing active pharmaceutical ingredients have aroused strong interests as they limit drugs polymorphism and improve their solubility. [29][30][31][32][33] API-ILs have also been used as solvent for poorly soluble drugs [34][35][36][37][38] and as drug delivery systems in the form of microemulsions [39] and micelles. [40] Drug delivery systems have also been obtained by immobilization of API-ILs into silica either by sol-gel processing, [41] adsorption to silica [42] or into biocompatible poly(L-lactic acid).…”
Section: Introductionmentioning
confidence: 99%